NALAR QIYAS PENGELUARAN ZAKAT PROFESI - Fahruddin, Achmad (Ekonomi Syariah STAI Sangatta Kutai Timur, 2024)
The profession of zakat is a type of maal zakat that emerged in this era. Regardless of the controversy over whether profession zakat is mandatory, it is imposed on every professional income that has reached its nisab. This study aims to determine how analogical reasoning (qiyas) is applied in the expenditure and calculation of professional zakat. This study is a type of library research. From the literature review found that there are two models of qiyas reasoning for profession zakat in determining its nisab and rate. First, profession zakat is analogized with the nisab of gold, which is 77.58 grams of gold, and its rate of 2.5% is paid after a year. Second, professional zakat is analogized with the nisab of agricultural zakat, which is 1323.132 kg of wheat or 815.758 kg of rice, and its rate of 5% is paid at harvest without waiting for a year. The 5% rate is determined assuming that all types of professions incur expenses during their operation.